Next generation amino acid technology for CO2 capture. Issue 3 (4th January 2021) - Xu, Xingguang; Myers, Matthew B.; Versteeg, Friso G.; Adam, Ethan; White, Cameron; Crooke, Emma; Wood, Colin D.
Abstract : A flexible strategy to prepare a scalable CO2 absorbent (LAHPs) via encapsulating amino acid salt solutions in a polymer matrix. Abstract : Amino acid salt (AAS) is a promising class of green material for CO2 capture due to its extremely low toxicity, negligible volatility and decent absorption capacity. However, the slow absorption kinetics and significant regeneration energy requirements hinder its widespread application. Here, for the first time, we present the encapsulation of AAS into solid polymer matrices to simply prepare a scalable material, namely liquid AAS hydrogel particles (LAHPs), for carbon capture. Owing to the enlarged contact area and more intense interaction between CO2 and the AAS, the absorption rate was significantly increased. Meanwhile, CO2 uptakes of LAHPs were improved, on average, by 40% compared to their stirred aqueous AAS solutions counterparts for a wide spectrum of AASs. Moreover, breakthrough experiments demonstrated that LAHPs had sufficient kinetics and capacity characteristics to be used across many fields such as post-combustion capture (15.0 vol% CO2 ), CO2 removal from enclosed systems ( e.g., submarines at 0.5 to 1.0 vol% CO2 ) and direct air capture of CO2, with CO2 uptake values of 62.8, 53.1, and 42.4 mg g −1 absorbent, respectively. For regeneration, low-grade steam proved to be an effective heating source for LAHPs regeneration, which could significantly decrease overall energy costs if the waste industrial steam was readily available. We have also explored replacing water with a higher boiling point polar solvent ( i.e. ethylene glycol). A 30 wt% solution of potassium sarcosinate in ethylene glycol can be infused into a cross-linked poly( N -hydroxyethyl acrylamide) hydrogel. Furthermore, with the use of a higher boiling point solvent ( i.e. ethylene glycol), the sorbent can be regenerated with minimal loss of solvent at 60 °C in a vacuum for 60 minutes. CO2 uptake capacities of 36.5 mg g −1 absorbent (average of 11 sorption–regeneration cycles) and 18.7 mg g −1 absorbent with pure CO2 and air, respectively, were obtained. Although the CO2 uptake of LAHPs is not among the highest reported, the simplicity of this approach may provoke ideas on the design of AAS-based CO2 absorbents that are green, versatile, readily scalable and economically regenerable.